Pengaruh Pola Asuh Orang Tua Terhadap Karakter Disiplin Anak Usia 4-5 Tahun - Endah Oktinawangsari; Luluk Asmawati; Laily Rosidah (Jurnal Kajian Anak (J-Sanak), 2023)
Parents play a crucial role in shaping a child's character and personality. The aim of this research is to determine the influence of parenting styles on the discipline character of 4-5 years old children at RA Asy-Syuhada, Central Jakarta. The method used is quantitative with an ex-post facto design. The study population consists of 32 children, and due to a saturation sampling technique, resulting in a sample size of 32 children. Data collection was conducted using questionnaires. Hypothesis testing was carried out using the t-test, and the result showed that the calculated t-count = 9.683 > t-table = 1.697, so it can be concluded that H₀ is rejected, and Ha is accepted. The results of the coefficient of determination in a simple linear regression test indicate that parenting styles have a 76.4% influence on a child's discipline character. The most dominant parenting style applied was the democratic parenting style, accounting for 93.75%, while the authoritarian was at 6.25%, and the permissive was at 0. Therefore, it can be concluded that parenting styles have a significant influence on the discipline character of 4-5 years old children at RA Asy-Syuhada, Central Jakarta. Keywords: Parenting Styles, Discipline Character, 4-5-Years Old Children